A Critical Review of Constraint-Induced Movement Therapy and Forced Use in Children With Hemiplegia. Issue 2 (2005) - Charles, Jeanne; Gordon, Andrew M.
Abstract : Hemiplegia is a physical impairment that can occur in childhood following head trauma, cerebral vascular accident or transient ischemic attack (stroke), brain tumor, or congenital or perinatal injury. One of the most disabling symptoms of hemiplegia is unilaterally impaired hand and arm function. Sensory and motor impairments in children with hemiplegia compromise movement efficiency. Such children often tend not to use the affected extremity, which may further exacerbate the impairments, resulting in a developmentally learned non-use of the involved upper extremity, termed 'developmental disuse'. Recent studies suggest that children with hemiplegia benefit from intensive practice. Forced use and Constraint-lnduced Movement Therapy (CI therapy) are recent therapeutic interventions involving the restraint of the non-involved upper extremity and intensive practice with the involved upper extremity. These approaches were designed for adults with hemiplegia, and increasing evidence suggests that they are efficacious in this population. Recently, forced use and constraint-induced therapy have been applied to children with hemiplegia. In this review, we provide a brief description of forced use and CI therapy and their historical basis, provide a summary of studies of these interventions in children, and discuss a number of important theoretical considerations, as well as implications for postural control. We will show that whereas the studies to date suggest that both forced use and CI therapy appear to be promising for improving hand function in children with hemiplegia, the data are limited. Substantially more work must be performed before this approach can be advocated for general clinical use.